Commercialization Phenomena of Reading the Holy Qur'an for Dead Person - Wibisono, M. Yusuf; Mulyana, Yana (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to exploit the phenomenon of commercialization of reading the verses of the Qur’an with the term wholesale who spend hundreds of thousands or even millions to carry out this event. The method used in this research is analytical descriptive with a qualitative approach while the nature of this study is grounded research, this research was conducted in Tugumukti Village, Cisarua District, West Bandung Regency. The results of this study are the practice of commercialization of reading the verses of the Qur’an among the people with varying amounts from hundreds to millions charged to heirs, the relationship used by them is a symbiotic mutualism which means mutual benefit from both the heirs or the cleric.